Shall we dance? Choreographing hospitality as key to interpersonal transformation - G.W. Marchinkowski (Acta Theologica)
The icon of the Holy Trinity by Andrei Rublev (1425) is a celebration of hospitality. This article contemplates the icon through Henri Nouwen’s eyes, using his methodology, and shows how the spiritual practice of hospitality is key to interpersonal transformation. The article considers Nouwen’s proposition that hospitality involved creating a space of true freedom in which the stranger can become a friend. It discusses Beatrice Bruteau’s view that such a free space required a communion paradigm in interpersonal relations, before investigating Nouwen’s unique metaphor for interpersonal transformation, a movement from hostility to hospitality. Finally, the article formulates principles for the spiritual practice of hospitality for ordinary people in everyday life, by considering the contributions of contemporary spiritual writers, Barbara Brown Taylor and Christine Pohl. Brown Taylor believes that the practice of hospitality began with paying attention, and Pohl warns against the challenges associated with its practice.